Printed ring slot antenna for circular polarization. - Kin-Lu Wong
A new design of a microstrip-line-fed circularly polarized printed ring slot antenna is proposed. Circular polarization (CP) radiation of the proposed design is achieved by introducing proper asymmetry in the ring slot structure and feeding the ring slot using a microstrip line at 45° from the introduced asymmetry. The asymmetry introduced in the proposed design is a meandered-slot section and the proposed CP design can be applied to printed square and annular ring slot antennas. Prototypes of the proposed design have been implemented. Experimental results show that good CP radiation performances are obtained and the 3 dB axial-ratio CP bandwidths obtained for the square and annular ring slot antennas are about 4.3% and 3.5%, respectively
Keywords: 1500 MHz; CP radiation performances; Asymmetry; Circular polarization; Meandered-slot section; Microstrip-line-fed circularly polarized printed ring slot antenna; Printed annular ring slot antennas; Printed square slot antennas; Ring slot structure